Maternal SSRI use during pregnancy and offspring depression or anxiety disorders: A review of the literature and description of a study protocol for a register-based cohort study - Upadhyaya Subina; Brown Alan; Cheslack-Postava Keely; Gissler Mika; Gyllenberg David; Heinonen Emmi; Laitinen Joonas; McKeague Ian; Hinkka-Yli-Salomäki Susanna; Sourander Andre; Tornio Aleksi; Malm Heli (Elsevier, 2025)
Previous studies examining the relationship between in utero exposure to selective serotonin reuptake inhibitors (SSRI) and long-term offspring depressive or anxiety behaviors are inconclusive. We aimed to critically review the findings of previous studies and describe a new study protocol to investigate the association of prenatal SSRI exposure and offspring depression or anxiety using data from several Finnish national registers. The study includes 1,266,473 mothers and their live-born singleton offspring, born in 1996-2018. The study cohorts include the prenatally SSRI exposed group and three comparison groups: 1) depression exposed/antidepressants unexposed, 2) unexposed to antidepressants or antipsychotics and depression, and 3) discordant siblings. We aim to examine whether depression in prenatally SSRI exposed children is more common or severe than depression in the offspring of mothers with depression but without SSRI exposure. We aim to disambiguate the effects of maternal SSRI from the effects of maternal depression, severity of maternal depression and familial loading history of psychiatric disorders by including data from first-degree relatives of prenatally SSRI exposed and unexposed children. Associations between exposure and outcome are assessed by statistical modeling, accounting for within-family correlation. The study has potential public health significance and in guiding clinicians in considering treatment options for pregnant women.